Association between the intake of α-linolenic acid and the risk of CHD. Issue 5 (14th September 2014) - Vedtofte, Mia Sadowa; Jakobsen, Marianne U.; Lauritzen, Lotte; O'Reilly, Eilis J.; Virtamo, Jarmo; Knekt, Paul; Colditz, Graham; Hallmans, Göran; Buring, Julie; Steffen, Lyn M.; Robien, Kimberly; Rimm, Eric B.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> The intake of the mainly plant-derived n-3 PUFA α-linolenic acid (ALA) has been reported to be associated with a lower risk of CHD. However, the results have been inconsistent. Therefore, the objective of the present study was to examine the association between the intake of ALA and the risk of CHD. Potential effect modification by the intake of long-chain n-3 PUFA (n-3 LCPUFA) was also investigated. Data from eight American and European prospective cohort studies including 148 675 women and 80 368 men were used. The outcome measure was incident CHD (CHD event and death). During 4–10 years of follow-up, 4493 CHD events and 1751 CHD deaths occurred. Among men, an inverse association (not significant) between the intake of ALA and the risk of CHD events and deaths was observed. For each additional gram of ALA consumed, a 15 % lower risk of CHD events (hazard ratios (HR) 0·85, 95 % CI 0·72, 1·01) and a 23 % lower risk of CHD deaths (HR 0·77, 95 % CI 0·58, 1·01) were observed. No consistent association was observed among women. No effect modification by the intake of n-3 LCPUFA was observed.